Technology offsets in international defence procurement - Balakrishnan, Kogila (Routledge studies in innovation, organization and technology, 2019)
Technology offsets, a nonconventional international trade-financing tool, is used by governments (buyers) to obtain industrial and technological benefits from companies (sellers) as part of international procurement. This book fills the gap in offsets and focuses on how to manage offsets more effectively by addressing issues of strategy, policy and implementation, technology management, governance and risk.